Novel contribution of cell surface and intracellular M1‐muscarinic acetylcholine receptors to synaptic plasticity in hippocampus. (9th June 2013) - Anisuzzaman, Abu Syed Md; Uwada, Junsuke; Masuoka, Takayoshi; Yoshiki, Hatsumi; Nishio, Matomo; Ikegaya, Yuji; Takahashi, Naoya; Matsuki, Norio; Fujibayashi, Yasuhisa; Yonekura, Yoshiharu; Momiyama, Toshihiko; Muramatsu, Ikunobu
Abstract: Muscarinic acetylcholine receptors (mAChRs) are well known to transmit extracellular cholinergic signals into the cytoplasm from their position on the cell surface. However, we show here that M1‐mAChRs are also highly expressed on intracellular membranes in neurons of the telencephalon and activate signaling cascades distinct from those of cell surface receptors, contributing uniquely to synaptic plasticity. Radioligand‐binding experiments with cell‐permeable and ‐impermeable ligands and immunohistochemical observations revealed intracellular and surface distributions of M1‐mAChRs in the hippocampus and cortex of rats, mice, and humans, in contrast to the selective occurrence on the cell surface in other tissues. All intracellular muscarinic‐binding sites were abolished in M1‐mAChR‐gene‐knockout mice. Activation of cell surface M1‐mAChRs in rat hippocampal neurons evoked phosphatidylinositol hydrolysis and network oscillations at theta rhythm, and transiently enhanced long‐term potentiation. On the other hand, activation of intracellular M1‐mAChRs phosphorylated extracellular‐regulated kinase 1/2 and gradually enhanced long‐term potentiation. Our data thus demonstrate that M1‐mAChRs function at both surface and intracellular sites in telencephalon neurons including the hippocampus, suggesting a new mode of cholinergic transmission in the central nervous system. Abstract : M1 muscarinic acetylcholine receptors (M1‐mAChRs) are G‐protein coupled receptors which predominantly exist in the brain and are involved in cognitive enhancement. In this issue, we found that M1‐mAChRs occur not only at synaptic and extrasynaptic surface membrane but also at intracellular sites in hippocampal pyramidal neurons, and may facilitate long‐term potentiation (LTP) with distinct signal cascades and on distinct timescales.